From commitment to practice: the EU response - Joanne van Selm; Madeline Garlick (Forced Migration Review, 2012)
Events in North Africa in 2011 transformed the pattern of boat arrivals in Europe – significantly in terms of the motivations of those arriving but with smaller numbers than might have been anticipated. The EU’s response indicates that more is needed to translate a commitment to solidarity from limited aid and statements of principle into practical reality